Macrophage TLR4 and PAR2 Signaling: Role in Regulating Vascular Inflammatory Injury and Repair - Rayees, Sheikh; Rochford, Ian; Joshi, Jagdish Chandra; Joshi, Bhagwati; Banerjee, Somenath; Mehta, Dolly (Frontiers in Immunology, 2020)
Macrophages play a central role in dictating the tissue’s response to infection and subsequent tissue repair. In this context, macrophages residing in the lungs continuously sense and discriminate between a wide range of insults to initiate immune response for host-defense. Inflammatory tissue injury also leads to activation of proteases and thereby coagulation pathway to optimize tissue response to injury and pathogens. However, long-lasting inflammatory trigger from macrophages can impair lungs’ ability to recover from severe injury leading to increased lung vascular permeability and neutrophilic injury, hall mark of Acute lung injury (ALI). In this review, we discuss the role of interplay between toll-like receptor4 (TLR4) and protease activating receptor 2 (PAR2) expressed on macrophage cell-surface in regulating lung vascular inflammatory signaling.